2019
DOI: 10.1080/10413200.2019.1647475
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Skills Used by Sport Psychology Consultants to Improve Their Consulting

Abstract: DECLARATION OF ORIGINALITY I hereby certify that I am the sole author of this thesis and that no part of this thesis has been published or submitted for publication. I certify that, to the best of my knowledge, my thesis does not infringe upon anyone's copyright nor violate any proprietary rights and that any ideas, techniques, quotations, or any other material from the work of other people included in my thesis, published or otherwise, are fully acknowledged in accordance with the standard referencing practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…The subscales have been reported to have a high degree of intercorrelation (r = .87) (Nwoga, Audu, & Obembe, 2016). Similarly, a high level of internal consistency (Intrusion:.87-.94, Avoidance: 84 -.87, Hyperarousal: = .79-.91) has been reported by previous studies (Cuijpers et al, 2020;Abel et al, 2018;Filion, Munroe-Chandler, & Loughead, 2021;Meggs & Mark, 2019;Vrijkotte et al, 2016;Clare et al, 2017;Elliot, 1999;Nicholls, 1984;Adeoya, Adeleye, & Egawa, 2021;Tashman, Simpson, & Cremades, 2018;Weiss & Marmar, 1997;Creamer et al, 2013). The authors reported a test-retest reliability coefficient of .89 to .94 after a 6-month interval (Weiss & Marmar, 1997).…”
Section: Methodsmentioning
confidence: 58%
“…The subscales have been reported to have a high degree of intercorrelation (r = .87) (Nwoga, Audu, & Obembe, 2016). Similarly, a high level of internal consistency (Intrusion:.87-.94, Avoidance: 84 -.87, Hyperarousal: = .79-.91) has been reported by previous studies (Cuijpers et al, 2020;Abel et al, 2018;Filion, Munroe-Chandler, & Loughead, 2021;Meggs & Mark, 2019;Vrijkotte et al, 2016;Clare et al, 2017;Elliot, 1999;Nicholls, 1984;Adeoya, Adeleye, & Egawa, 2021;Tashman, Simpson, & Cremades, 2018;Weiss & Marmar, 1997;Creamer et al, 2013). The authors reported a test-retest reliability coefficient of .89 to .94 after a 6-month interval (Weiss & Marmar, 1997).…”
Section: Methodsmentioning
confidence: 58%
“…Goal-directed self-talk research focuses on statements that reflect controlled mental processes that are consciously used for self-regulation, problem-solving, and rational thinking. According to the descriptors used in many goal-directed self-talk studies, this type of self-talk is thought of as a self-regulation strategy (Littlewood et al, 2018; Neck & Manz, 1992) that takes a verbal form (Lin, 2017; Manfra et al, 2014) or as a psychological skill (Filion et al, 2019; Kirschenbaum et al, 1998). This usage is clearly in line with the definition of goal-directed self-talk as a self-regulatory mechanism that is used intentionally and effortfully to make progress on a task, whether writing an essay or pursuing the acquisition of self-knowledge (Latinjak et al, 2014).…”
Section: Self-talk Literature Reviewmentioning
confidence: 99%
“…Nevertheless, from the information provided in most articles, it was difficult to know which of these three criteria was used to name selftalk. For example, the most popular self-talk labels, positive self-talk and negative self-talk (Table 1), could reflect the Inner dialogue 14,16,17 Also: Dialogical ST 9 Overt ST 6,17,18 or private speech 6,17,18 Covert ST 17 or inner speech 18,19 b) … ST content and types of self-statements of both goal-directed and spontaneous ST. Spontaneous ST 54,59 Also: Undirected ST 54 Negative ST 41,43,44,45,46,48,50,51,53,55,57,60 Anxious ST 42,45,46,48,49,55 Depressive ST 42,45,46 Positive ST 41,43,46,51,52,53,60 Goal-directed ST research Also: Rational ST 25 Positive ST …”
Section: The Focused Reviewmentioning
confidence: 99%
“…In my planning, I also noted down some cue words (e.g. be present) that I would say to myself to help me remain focused on the client and listen attentively (Filion et al, 2021).…”
Section: Reflections and Summarymentioning
confidence: 99%